POLIANDRI PADA MASYARAKAT: STUDI KASUS PENGADILAN AGAMA PARIAMAN - Makmur Syarif (Universitas Islam Negeri Imam Bonjol Padang, 2016)
The purpose of this research is to determine factors that cause Poliandry cases, both lead some people to chooce and facilitate poliandry in Padang Pariaman. Qualitative research by using normative law or doctrinal law methods was used. data taken from interview to some informants was analyzed thematically based on the indicators of the study. The result of the study showed that some factors may facilitate people to have poliandry. They are the low educational level, the willingness to make the marital commitement, both the view of figh and positive law. The cases of Poliandry especially for write recorded marriage, and divorce are due to the the lack of comprehension on the a marriage legallity and illegallity beside the knowledge limitattion related with the ban in a marriage before a divorce formally or legally approved. It could be considered by the the office of religious court to educate its societies on the effect of Poliandry.